1995
DOI: 10.1096/fasebj.9.2.7781930
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle glycolytic and oxidative enzyme capacities are determinants of insulin sensitivity and muscle composition in obese women

Abstract: Regional fat distribution is an important determinant of insulin resistance in obesity. In the current study, the relationship between skeletal muscle insulin sensitivity, mid-thigh muscle composition, and the metabolic profile of muscle was investigated. Muscle composition was assessed by computed tomography of the mid-thigh, and by activities of marker enzymes of aerobic-oxidative and glycolytic pathways and muscle fiber typing using biopsies of the vastus lateralis muscle. Muscle with reduced Hounsfield att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
273
3
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(294 citation statements)
references
References 0 publications
16
273
3
2
Order By: Relevance
“…At rest, skeletal muscle is the primary site of insulin-stimulated glucose disposal 20 and there is increasing evidence that high muscle fat stores may play an important role in insulin resistance. 4,5,21,22 Conversely, when energy expenditure is considered, only about 28% of total energy expenditure can be accounted for by skeletal muscle. 23 Therefore, change in muscle fat oxidation at rest is likely to have a rather minor impact on whole body fat oxidation rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At rest, skeletal muscle is the primary site of insulin-stimulated glucose disposal 20 and there is increasing evidence that high muscle fat stores may play an important role in insulin resistance. 4,5,21,22 Conversely, when energy expenditure is considered, only about 28% of total energy expenditure can be accounted for by skeletal muscle. 23 Therefore, change in muscle fat oxidation at rest is likely to have a rather minor impact on whole body fat oxidation rate.…”
Section: Discussionmentioning
confidence: 99%
“…Second, CT results also suggest that women with a high muscle triglyceride content present a lower muscle citrate synthase activity (which is an index of muscle oxidative capacity) and insulin resistance. 5 On the other hand, an increase in intracellular muscle fat stores may facilitate the contact between intracellular fat stores and mitochondria and lead to an increase in fat oxidation rate. 6 In the present study, low attenuation muscle (LAM), assessed by CT, represents skeletal muscle enriched with diffuse fat stores, which are too small to be detected as distinct entities in a CT scan but important enough to reduce the attenuation of the muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Physical inactivity can lead to obesity, insulin resistance and Type 2 diabetes. Insulin resistance is associated with many abnormalities in muscle tissue such as an increase in muscle lipid content, impaired glycogen synthesis, an enzymatic disposition towards anaerobic generation of energy (high PFK/CS ratio), an increase in the proportion of Type 2 muscle fibres and a reduced capillary density [9,10,11,63,64]. These abnormalities could contribute to the lower VO 2max often seen in Type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Colberg et al, 15 showed that women with visceral obesity have reduced FFA utilization in muscle in the postabsorptive state. Furthermore, Colberg et al 15 and Simoneau et al 16 found that obese women have a decreased oxidative capacity and increased glycolytic and anaerobic capacities of skeletal muscle. This may suggest that not FFA availability in blood, but rather the oxidative enzymes in skeletal muscle may be the limiting factor for the increase in lipid oxidation and thermogenesis.…”
Section: Introductionmentioning
confidence: 99%